(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2018)
E-learning is defined as a learning tool that is supported by information and communication technology. In the last ten years, E-learning has become the key issue of universities all over the world and has a significance impact on current higher education. The issue of utilizing novel information and communication technologies for teaching and learning, is therfore crucial. Before implementing an E-learning framework in Jeddah university, a questionnaire is established to highlight the ability of teachers’ to use this new way of education or not. The results show that the teachers have favorable attitude towards the use of E-learning and new technologies to enhance the education.